Structural characterization, optical properties and photocatalytic activity of MOF-5 and its hydrolysis products: implications on their excitation mechanism - Rodríguez, N. A. (2015)
The existing concerns on the limited stability of Zn4O-based MOFs upon exposure to humidity or aqueous environments, as well as on the excitation mechanisms, are discussed on the basis of Raman, FTIR, DR-UV and XRD measurements. This paper demonstrates that MOF-5 dispersed in water produces a relatively stable new phase, MOF-5W, which slowly degrades to MOF-5H, a mixture of MOF-5W and zinc terephthalate dihydrate (ZTDH). The structure and optical properties of MOF-5W and MOF-5H and their optical and photocatalytic properties reveal the main role played by the organic moiety in determining the final properties of these structures, supporting the idea of a ligand to ligand charge transfer (LLCT) excitation mechanism rather than the usually assumed ligand to metal charge transfer (LMCT).